LA MOBILITE INTERNE DE LA MAIN D’ŒUVRE FEMININE EN ALGERIE - Souhila Hamoudi; Fouzia Hider (Social Empowerment Journal, 2019)
Addressing the issue of women's migration is a very interesting subject. Nowadays, Migration is not just about the circulation of women and their facilities in a region other than their own, but it also reflects the upheavals in women's lives. the personal, professional and cultural lives of immigrant women and the reorganization efforts of a new life adapted to the economic and social structures of the host regions.In this article, we present the results of a field survey of a sample of 86 women who came to the wilaya of Bejaia from different other wilaya of Algeria, in order to understand the reasons and process of socioprofessional integration of female labor migration.